Gambaran Efek Sevoflurane Terhadap Tekanan Darah pada Pasien General Anestesi - Martunus Juddin; Sulastri Sulastri; Vira Aryana Teruruano Malengga (Universitas Muhamadiyah Manado, 2024)
Ceflurane, which is a halogenated ether, is packaged in liquid form, colorless, non-explosive, odorless and non-irritating so it is good for inhalation induction. find out the effect of sevoflurane on blood pressure in patients under general anesthesia. The design of this study is a quantitative type using a descriptive approach with a population of 36 people The sample used in this study is purposive sampling with as many as 33 respondents This research was conducted at Ibnu Sina Hospital,Gresik Regency during February-May 2024. The variable in this study is an overview of the effect of sevoflurane on blood pressure. An overview of the effect of sevoflurane on blood pressure showed that of the 33 respondents, they had a blood pressure of 15 minutes after being given sevoflurane with an average of 113.36, a median of 114.00, a standard deviation of 10.977 with the blood pressure of general patients after being given sevoflurane at least 93 mmHg and a maximum of 140 mmHg. Based on the study, the picture of the effect of sevoflurane on blood pressure in general anesthesia patients decreased.